2018
DOI: 10.1002/eap.1710
|View full text |Cite
|
Sign up to set email alerts
|

Severe fire weather and intensive forest management increase fire severity in a multi‐ownership landscape

Abstract: Many studies have examined how fuels, topography, climate, and fire weather influence fire severity. Less is known about how different forest management practices influence fire severity in multi-owner landscapes, despite costly and controversial suppression of wildfires that do not acknowledge ownership boundaries. In 2013, the Douglas Complex burned over 19,000 ha of Oregon & California Railroad (O&C) lands in Southwestern Oregon, USA. O&C lands are composed of a checkerboard of private industrial and federa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(137 citation statements)
references
References 99 publications
6
120
1
Order By: Relevance
“…)—which dramatically changed fire behavior and greatly improved the effectiveness of suppression efforts. Mean daily burning index (BI) for the first 4 d of the fire was 52–76, which was above the historic (1991–2017 1 June–30 September) 90th percentile for this period (Zald and Dunn ). Mean daily energy release component (ERC) values ranged from 49 to 67, also above the 90th percentile for this area (Dalton et al.…”
Section: Methodsmentioning
confidence: 80%
See 3 more Smart Citations
“…)—which dramatically changed fire behavior and greatly improved the effectiveness of suppression efforts. Mean daily burning index (BI) for the first 4 d of the fire was 52–76, which was above the historic (1991–2017 1 June–30 September) 90th percentile for this period (Zald and Dunn ). Mean daily energy release component (ERC) values ranged from 49 to 67, also above the 90th percentile for this area (Dalton et al.…”
Section: Methodsmentioning
confidence: 80%
“…, Donato et al. , Thompson and Spies , Zald and Dunn ). High‐severity wildfire can alter soil and successional pathways and potentially shift the system into an alternative stable state (Peterson ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Many studies had reported the significant negative impact of heat and drought events in planted forests (Goldstein et al, ; Migliavacca et al, ; Sun, Wen, Yu, Liu, & Liu, ). Comparisons between managed forests and their counterpart natural forests also revealed that their response to the same extreme event could be opposite (van Gorsel et al, ; Zald & Dunn, ). Other studies have indicated that resistance of forests to climate extremes is determined by the species composition and stand density (Arthur & Dech, ; Giuggiola, Bugmann, Zingg, Dobbertin, & Rigling, ).…”
Section: Discussionmentioning
confidence: 99%